HIRUDINEOS DE MEXICO XVI NUEVOS HUESAN LUIS POTOSIEDES Y LOCALIDADES PARA ALGUNAS SANGUIJUELAS YA CONOCIDAS Y DESCRIPCION DE UNA NUEVA ESAN LUIS POTOSIECIE - CABALLERO Y C, EDUARDO; C, EDUARDO (Rockefeller Foundation, CD MEXICO, DF, MEX, 1942)
Species of parasitized birds, where found, and organs showing Microfilaria are given in a chart The parasites were not classified, and the smears are available to anybody who wishes to study them further
ANS INST BIOL
Keywords: HIRUDINEOS, MEXICO XVI, NUEVOS HUESPEDES, LOCALIDADES, SANGUIJUELAS, DESCRIPCION, NUEVA ESPECIE; CIENCIAS DE LA VIDA; BIOLOGIA ANIMAL; COMPORTAMIENTO ANIMAL